(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to investigate the effect of somegrowth regulators on in vitro shoot regeneration, multiplication androoting of Chrysanthemum morifolium to develop a protocol for its masspropagation. Nodal explants of C. morifolium were cultured on MS basalmedium supplemented with the cytokinins BAP and kinetin, both at 0.0,0.1, 0.2, 0.5, 1.0, 2.0, 5.0, 10.0 mg/l, for shoot regeneration. Theregenerated shoots were separated from the nodal explants and culturedon MS medium supplemented with BAP and kinetin, both at 0.0, 0.1, 0.2,0.5 mg/l for shoot multiplication. The shoots were then cultured on MSmedium supplemented with 0.0, 0.1, 0.2, 0.5 mg/l of IBA for rooting.Twenty explants were used per treatment. The percentage of respondedexplants, average number of shoots per explant, length of shoot,percentage of rooted shoots, number of roots per shoot and length of rootwere determined. The concentration of 0.1 mg/l of both BAP and kinetinshowed the best response with regard to shoot regeneration andmultiplication giving the highest number of shoots per explant.Cytokinin–free medium gave significantly the highest length of shoot. AllIBA treatments gave 100% rooting. However, MS+ 0.5 mg/l IBA resultedin significantly the highest number of roots per shoot, and IBA–freemedium resulted in significantly the highest root length